2014
DOI: 10.4209/aaqr.2012.08.0218
|View full text |Cite
|
Sign up to set email alerts
|

Investigations of Transported and Local Emissions on Particle Compositions in Korea

Abstract: The synoptic meteorological patterns, aerosol optical thickness (AOT) and changes in the chemical composition of aerosol particles are indicators that allow the study of the effects of emissions on air quality. These approaches have been applied to two sets of intensive campaign measurement data in Gwangju, Korea, allowing the identification of long-range transported

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 35 publications
(47 reference statements)
0
2
0
Order By: Relevance
“…Therefore, concentrations of DEE-related BC and PM 2.5 in cities is expected to be increased with the number of diesel vehicle registrations. Several previous studies reported temporal and spatial variations of PM 2.5 concentrations or characteristics of PM 2.5 measured at national air quality monitoring sites or a PM 2.5 monitoring supersite South Korea [ 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, concentrations of DEE-related BC and PM 2.5 in cities is expected to be increased with the number of diesel vehicle registrations. Several previous studies reported temporal and spatial variations of PM 2.5 concentrations or characteristics of PM 2.5 measured at national air quality monitoring sites or a PM 2.5 monitoring supersite South Korea [ 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Because of this, any follow-up study that involves actual in situ PM 2.5 measurements must also include chemical analysis of sampled particulates as well as source apportionment in order to determine the actual amounts of air pollutants by source. A reference study was conducted by Cayetano et al (2014a), and research projects with methodologies similar to this study are currently being conducted in Cabanatuan and other cities.…”
Section: Recommendationsmentioning
confidence: 99%